The collective action for water in colombia and the referendum as direct democracy approach (2014)
The analysis of collective action in defense of water takes up the history of mobilization in the country from 1909 to 2009, the management of community aqueducts, and consolidated the use of legal tools, up to the referendum on the water as significant moment of mobilization, identifying how causes change with privatization, legislation and marketing of commons and services of natural resources, carrying to a time of political commitment and a participatory and direct democracy, to the consecration of water as a human right, through a referendum of a citizens' initiative, placing the issue on the public agenda with access to a basic minimum of water as a mechanism to achieve the right to water, the strengthening of community aqueducts and discussion about the legislative process of the referendum.